The Influence Of E-Service Quality Dimensions On E-Customer Satisfaction And Its Impact On E-Customer Loyalty Tiket.Com - Athallah Naufal, Muhammad; Millanyani, Heppy; Trianasari, Nurvita (Publisher Cv. Inara, 2024)
The problem that is often experienced by companies in the field of online transportation services such as travel agencies is the quality of service provided. Most consumers are dissatisfied with the services provided. These problems make researchers interested in further examining the level of consumer satisfaction with the services provided and analyzing consumer loyalty in using the travel agency application in the form of tiket.com. The implementation of this research implements a descriptive quantitative method with the data collection technique, namely a questionnaire. Then the sample selection method applies non-probability sampling of the purposive sampling type and 260 respondents are obtained. While the data analysis implements hypothesis testing in the form of SEM-PLS. Based on the test results and analysis conducted, it was found that 1) e-customer satisfaction is positively influenced insignificantly by site organization; 2) e-customer satisfaction is not positively influenced by efficiency; 3) e-customer satisfaction is positively influenced insignificantly by responsiveness; 4) e-customer satisfaction is positively influenced by user friendliness; 5) e-customer satisfaction is positively influenced insignificantly by personal needs; 6) e-customer satisfaction is positively influenced by fulfillment; and 7) e-customer satisfaction is positively influenced by security